Analisis Framing Pemberitaan Media TvOne News dan VIVA.co.id Atas Ancaman Terhadap Vonis Mati Ferdy Sambo - Ghifari, Naufan; Satria, Raden Ariq Wahyu (Borobudur Communication Review, 2023)
This study aims to analyze the news regarding the death sentence against Ferdy Sambo in forming a point of view in reporting on two online media, namely TvOne News and VIVA.co.id in the period January 24 2023 to February 19 2023. Framing analysis was carried out in this study. This study uses the framing analysis model of William A. Gamson and Andre Modigliani. According to William A. Gamson and Andre Modigliani, framing is divided into two, namely: framing devices and resuming devices. Framing devices consist of five types: metaphors, exemplars, catchphrases, depictions, and visual images. Meanwhile, the resuming device consists of two types: roots and appeal to principle. The results of this study show that each news item is found on the online media TvOne News and VIVA.co.id. There must be some element of analytical material found in the news. The two online media are TvOne News and VIVA.co.id. jointly framing or framing the issue of the death sentence against Ferdy Sambo and the institution of the National Police.